FAULT DETECTION AND PROTECTION METHOD ON LOW VOLTAGE DC MICRO-GRID SYSTEM - Sholeh Hadi Pramono; Eka Maulana; Hadi Suyono; Akhmad Zainuri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2018)
ABSTRACTMicro-grid architecture is designed for small scale model in Brawijaya University area in order to change conventional AC-based electricity system previously. Low voltage direct current (LVDC) levels are proposed and charactized to obtain the optimal design of the DC grid system. Some parameters related to the electrical phenomenon of voltage, current and power which occur in distributed-generation, distribution grid, and load sites were also analyzed. Detailed model of photovoltaic (PV) and PMSG was implemented with operational analysis and simulated with study case modes to achieved the power and system efficiency. DC bus is conducted to accommodate the distribution power between PV generation, battery and super capacitor for energy sorage element, distributed-load and other grid utilization.Various condition and operation have been characterized toward stability performance of the voltage and current of 12-36 volts and 0-20 A DC, respectively. This architectural design can be utilized to develop an actual design and small scale implementation of the LVDC smart micro-grid system.Keywords: Fult Detection Protection Micro-grid Low Voltage DC